Semi-automatic building of wordnet for Bangla - Roy, Mritunjoy Chandra Saha; Muqtadir, Maruf (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.